Resection of unresectable hepatocellular carcinoma after conversion therapy with apatinib and camrelizumab: a case report and literature review - Liu, Xin-Liang; Li, Xiang-Ze; Chu, Yi-Fu; Liu, Feng; Tian, Hu (Frontiers in Oncology, 2024)
Hepatocellular carcinoma is a rather common malignant tumor. Most patients with hepatocellular carcinoma receive their diagnosis at an advanced stage, at which surgical resection is no longer appropriate. A growing body of research has demonstrated the value of convention therapy for patients with intermediate-stage hepatocellular carcinoma, while specific application protocols and treatment guidelines are not well developed. Emerging clinical researches suggest that a tyrosine kinase inhibitor in combination with an immune checkpoint inhibitor is a reasonable strategy for unresectable hepatocellular carcinoma. However, there are relatively few reports on the efficacy of apatinib and camrelizumab in the treatment of hepatocellular carcinoma. We were able to successfully remove one patient’s hepatocellular carcinoma after 8 cycles of conversion therapy with apatinib (250 mg orally every day) and camrelizumab (200 mg intravenously every 2 weeks). The patient continued to receive the same dose of 16 cycles of apatinib and camrelizumab after hepatectomy. By the time of this study, the patient has completed 18 months of follow-up, and no tumor recurrence or metastasis was found in tumor markers and imaging examinations. Apatinib in combination with camrelizumab is an effective therapy for the treatment of advanced hepatocellular carcinoma, and surgical resection after this conversion therapy may provide patients with long-term oncological benefits. However, this requires more samples to validate the conclusion.